Back to the basics: cnidarians start to fire - Bosch, Thomas C. G.; Holstein, Thomas W.; Jékely, Gáspár (Trends in neurosciences, 2017)
The nervous systems of cnidarians, pre-bilaterian animals that diverged close to the base of the metazoan radiation, are structurally simple and thus have great potential to reveal fundamental principles of neural circuits. Unfortunately, cnidarians have thus far been relatively intractable to electrophysiological and genetic techniques and consequently have been largely passed over by neurobiologists. However, recent advances in molecular and imaging methods are fueling a renaissance of interest in and research into cnidarians nervous systems. Here, we review current knowledge on the nervous systems of cnidarian species and propose that researchers should seize this opportunity and undertake the study of members of this phylum as strategic experimental systems with great basic and translational relevance for neuroscience.
Available online 30 December 2016
Gesehen am 17.11.2018